Effects of 5-HT1A-Receptor Agonist, 8-OH-DPAT, and GABAB-Receptor Agonist, Baclofen, on Lordosis in Female Rats With Lesions in Either the Dorsal Raphe Nucleus or Septum - Miki Kishitake; Korehito Yamanouchi (Elsevier, 2005)
The inhibitory effects of 8-OH-DPAT, a 5-HT1A-receptor agonist, and baclofen, a GABAB-receptor agonist, on lordosis were examined in estrogen and progesterone-treated ovariectomized rats with lesions in either the dorsal raphe nucleus (DRN) or septum and in rats with either sham lesions or no lesions. The first behavior test series was carried out 6 days after implantation of the rats with silicon tubes containing estradiol. Four hours after injection with 0.5 mg progesterone, behavioral tests were performed before and 30 min after an injection with 1mg/kg body weight 8-OH-DPAT. As a result, the mean lordosis quotient (LQ)s were changed from 100 to less than 20 before and after the injection in all groups. These results suggest that 8-OH-DPAT acts on areas other than the DRN and the septum, leading to a decrease in lordosis. Two weeks after implantation with estradiol, the next behavioral test series was carried out after injection with progesterone. Behavioral tests were performed before and after an injection with 10 mg baclofen. The results showed that the mean LQs decreased after the injection in all groups, but the mean LQ in the DRN lesion group was higher than that in the sham groups. These results indicate that baclofen may act partially on the DRN in inhibiting lordosis in female rats. Keywords:: lordosis, 5-HT1A-receptor agonist, GABAB-receptor agonist, dorsal raphe nucleus lesion, septal lesion